Banking Sector Accounting Practices and Financial System Stability (gjstudies, 2017)
This paper investigates the underexplored nexus between heterogeneous accounting practices within the banking sector and the emergent stability properties of the financial systemas a whole. Departing from traditional analyses that treat accounting as a neutral, transparent reporting mechanism, we conceptualize accounting frameworks as active, constitutiveelements of the financial ecosystem that shape bank behavior, risk perception, and interbankdynamics. Our novel contribution lies in modeling the financial system as a complex adaptivenetwork where nodes (banks) employ one of three distinct accounting paradigms: HistoricalCost Accounting (HCA), Fair Value Accounting (FVA), and a proposed hybrid, DynamicProvisioning Accounting (DPA). We develop an agent-based computational model to simulate the propagation of liquidity and solvency shocks under varying compositions of theseaccounting practices. The model incorporates feedback loops where reported accounting figures directly influence market confidence, collateral values, and interbank lending decisions,thereby endogenizing systemic risk. Our results reveal several non-linear and counterintuitive findings. First, a system predominantly using FVA exhibits higher volatility and fastershock transmission, confirming some post-crisis critiques, but also demonstrates a greatercapacity for early loss recognition and rapid system cleansing. Second, a homogeneous HCAregime fosters apparent short-term stability but can lead to the accumulation of hiddenlosses and larger, delayed systemic collapses—a ’stability illusion.’ Third, and most originally, we find that a deliberately heterogeneous mix of accounting practices, particularly onethat strategically embeds DPA banks as ’circuit breakers,’ can enhance systemic resilience bydampening pro-cyclical feedback and creating asynchronous response mechanisms to shocks.The optimal mix is non-trivial and depends on network topology and shock origin. We conclude that financial system stability is not merely a function of individual bank capital but isprofoundly mediated by the diversity and design of the accounting rulebook itself. This argues for a macroprudential approach to accounting standard-setting that considers systemicnetwork effects, moving beyond the micro-level ’representational faithfulness’ paradigm thathas dominated standard-setting discourse.